2019
DOI: 10.3758/s13415-019-00742-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in neural activation and functional connectivity during the processing of vocal prosody in adolescence

Abstract: The ability to recognize others' emotions based on vocal emotional prosody follows a protracted developmental trajectory during adolescence. However, little is known about the neural mechanisms supporting this maturation. The current study investigated age-related differences in neural activation during a vocal emotion recognition (ER) task. Listeners aged 8 to 19 years old completed the vocal ER task while undergoing functional magnetic resonance imaging. The task of categorizing vocal emotional prosody elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 113 publications
(132 reference statements)
1
9
0
Order By: Relevance
“…, 2005 ). An increase in dmPFC response to vocal emotion is broadly consistent with cross-sectional age-related changes in this sample that have been previously reported ( Morningstar et al. , 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…, 2005 ). An increase in dmPFC response to vocal emotion is broadly consistent with cross-sectional age-related changes in this sample that have been previously reported ( Morningstar et al. , 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…, 2009 , 2012 ). Previous work by our group noted age-related changes in the involvement of such social cognitive regions in a vocal ER task ( Morningstar et al. , 2019 ).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, although this small magnitude interaction effect should be interpreted with caution until it is replicated in a larger sample, we found that group differences in vocal ER were particularly pronounced in younger participants. Struggling to identify the emotional intent of peer-aged speakers has been linked with poorer psychosocial outcomes in typically developing youth ( Maxim and Nowicki, 2003 , McClure and Nowicki, 2001 , Morningstar et al, 2019b , Nowicki and Carton, 1997 , Nowicki and Duke, 1992 , Rothman and Nowicki Jr., 2004 ); as such, this form of deficit may be contributing to social difficulties commonly experienced by children with epilepsy ( Camfield and Camfield, 2007 , Drewel and Caplan, 2007 , Sillanpää and Helen Cross, 2009 , Steiger and Jokeit, 2017 ). However, additional research will be needed to determine the functional consequences of vocal ER deficits in youth with epilepsy.…”
Section: Discussionmentioning
confidence: 99%